The effect of death anxiety on orthorexia nervosa tendencies in type 2 diabetes patients - Öztürk, Zeynep; Turan, Gülcan Bahçecioğlu; Aksoy, Meyreme (My University, 2024)
Aim: This study was conducted to investigate the effect of death anxiety on orthorexia nervosa tendencies in patients with Type 2 diabetes. Materials and Methods: This study was conducted with 200 Type 2 diabetes patients who referred to internal medicine outpatient clinics of a university hospital in Elazığ, a city in the east of Turkey. The data were collected by using “Descriptive Information Form”, “Death Anxiety Scale (DAS)” and “Orthorexia-11 Scale (ORTO-11)”. Results: The mean DAS score of the patients was 11.41±2.09, while their mean ORTO-11 score was found as 23.69±6.09. It was found that DAS total score was a significant and negative predictor (?= -.540, p<0.001) and explained 29 % of ORTO-11 total score. Conclusion: Patients with Type 2 diabetes were found to have high level of death anxiety and moderate level of orthorexia nervosa tendency. It was found that orthorexia nervosa tendency increased as death anxiety increased.
Keywords: Diabetes mellitus; Nursing; Death; Feeding and Eating Disorders